Analisis Ketimpangan Sosial dan Strategi Perekonomian Pedagang Pendatang di Pantai Kuta, Bali - Asnimawati; Alya Dewi Nasution; Nihayatus Sa'adah; Firgian Nazala; Razita Atsilah; Aurora Meilinda Sagita; Sugiantoro; Andiva Nailus (Universitas Pendidikan Ganesha, 2025)
This study explores the socio-economic disparities encountered by migrant traders in the tourist area of Kuta Beach, Bali. The inequality includes limited access to business spaces, lack of legal recognition, and exclusion from social assistance and formal protection. Using a qualitative approach and case study method, data were gathered through direct observation, in-depth interviews, and document analysis. The findings indicate that local traders benefit from privileged access to economic spaces, while migrant traders experience structural disadvantages that increase their financial burdens. Despite these challenges, migrant traders respond with adaptive economic strategies such as product innovation, business diversification, informal networking, and price flexibility. These actions reflect their economic agency within an unequal system. The study highlights the urgency of inclusive policy reforms and equitable spatial management to ensure social justice and economic resilience in tourism-driven communities.